Collusion in Uniform-Price Auctions: Experimental Evidence and Implications for Treasury Auctions - Goswami, Gautam; Noe, Thomas H.; Rebello, Michael J. (Review of Financial Studies, 1996)
We provide experimental evidence that nonbinding preplay communication between bidders in auctions of shares facilitates the adoption of equilibrium strategies: collusive strategies in uniform-price auctions, and the unique equilibrium in undominated strategies in discriminatory auctions. When communication between bidders is introduced, clearing prices and auctioneer profits in uniform-price auctions fall below those observed in discriminatory auctions. This evidence suggests that uniform-price auctions of Treasury securities may result in lower revenues than the currently employed discriminatory procedure.